Europe’s 21st century performance and its engagement with postmodern culture: difference and event - Orosa, Miguel A. (European Public & Social Innovation Review, 2024)
Introduction: This paper, from a poststructuralist approach of event and, besides, of difference (keys transversal to postmodernity and affecting the performative phenomena), intends to set up a theoretical framework out of the "problematic", from the question and the plight, rather than on the basis of the so-called apodictic, out of what is necessarily valid. This model to which we refer, made up of several philosophical concepts from current thought, tries to provide some keys from which to catch the so-called "performance" in the European stage of the 21st century. Methodology: An analysis of the performances in their constituent parts is carried out, and then the common data are synthesized in order to draw relevant conclusions. Results and Conclusions: The philosophical-performative model, compared and analyzed with the performances of representative groups on the European continent, is validated. Discussion: While interpreting the results and bringing them into contact with our transdisciplinary theoretical-factual corpus (the fruit of philosophical-dramatic research, of conversations and experiences in the field of dramaturgy and also of the stage), we observe not only that the variables are validated and meet the criteria of performativity, but also that it is not possible to understand this phenomenon apart from its postmodern grassroots.